Species and antifungal susceptibility profile of agents causing vulvovaginal candidiasis in a military population: a cross-sectional study. (9th March 2023) - Trajano, Débora Thaís Moreira; Melhem, Márcia de Souza Carvalho; Takahashi, Juliana Possatto Fernandes; Bonfietti, Lucas Xavier; de Araújo, Miriam Randó; Corrêa, Viviane Barbosa; Araújo, Karina Basseto de Oliveira; Barnabé, Viviani; Fernandes, Carolina Gonçalves
Abstract: Military women on active duty are exposed to constant physical and mental demands, which may predispose them to some infection risks, including vulvovaginal candidiasis (VVC), a pathology considered a global public health problem. To monitor the prevalent and emerging pathogens in VVC, this study aimed to evaluate the distribution of yeast species and their in vitro antifungal susceptibility profile. We studied 104 vaginal yeast specimens obtained during routine clinical examinations. The population was attended at the Medical Center of the Military Police, São Paulo, Brazil, and was divided into two groups: infected patients (VVC) and colonised patients. Species were identified by phenotypic and proteomic methods (MALDI-TOF MS) and susceptibility to eight antifungal drugs, including azoles, polyenes, and echinocandins, was determined using microdilution broth. Candida albicans stricto sensu was found to be the most frequently isolated species (55%), but we observed a considerable rate of other Candida species isolates (30%), including Candida orthopsilosis stricto sensu only in the infected group. There were also other rare genera such as Rhodotorula, Yarrowia, and Trichosporon (15%), of which Rhodotorula mucilaginosa was the most prevalent in both groups. Fluconazole and voriconazole had the highest activity against all species in both groups. Candida parapsilosis was the most susceptible species, except for amphotericin-B in the infected group. Of note, we observed unusual resistance in C. albicans . Our results have allowed us to compile an epidemiological database on the etiology of VVC to support the empirical treatment and improve the health care of military women. Lay Summary: Vulvovaginal candidiasis (VVC) is an infection caused by fungi, mainly Candida albicans . Our results show that fungi other than C. albicans can cause VVC. So, our findings may help to choose the most appropriate treatment, as some may be resistant, to improve the quality of life of military women.